Pre-prosthetic orthodontics - Hayam Alfallaj (Saudi Dental Journal)
For some patients, pre-prosthetic orthodontic intervention is necessary to optimize both esthetic and functional aspects of dental treatment. This review will focus on the following topics: orthodontics treatment with multiple missing teeth, correction of anterior deep vertical overlap, anterior worn dentition, up-righting of tilted teeth, and orthodontic crown lengthening. This review will aid restorative dentists in identifying which patients could benefit from orthodontic intervention, and in understanding how orthodontic treatment can be utilized to improve patient prognosis in restorative treatment. Keywords: Orthodontics, Interdisciplinary, Crown-lengthening, Worn-teeth, Tilted-molar